Pemahaman Internet sebagai Pemoderator: Pengaruh Literasi Pajak dan E-Filing terhadap Kepatuhan Pajak - Sholikhati, Niken Gladis; Umaimah, Umaimah (Jurnal Ilmiah Akuntansi dan Finansial Indonesia, 2024)
Examining the impact of tax literature and e-Filing use on taxpayer adherence with internet understanding as a moderate is the goal of this study. Individual taxpayers (WPOP) who submit Annual Tax Return (SPT) reports via e-filing in Gresik City are the populace of this study. Sampling of 72 respondents through simple random sampling method. Structural Equation Model with SmartPLS 4.1 software was used to analyze the data. The findings in the study indicate that tax literacy and the use of e-filing have a positive effect on taxpayer compliance, but internet understanding is unable to moderate the bond between tax literacy and the use of e-filing on tax compliance in Gresik City.